Genomics of insecticide-metabolizing bacteria associated with Spodoptera frugiperda (Lepidoptera: Noctuidae) and their potential role in host detoxification - Gomes, Ana Flavia Freitas (2024)
The evolutionary success of the class Insecta can be partially attributed to its association with bacteria. Association with non-pathogenic microorganisms ensures the maintenance of complex phenotypes, with host and microbiota that respond together to adverse environmental conditions. In previous studies, we have shown that insecticide-resistant strains and natural populations of Spodoptera frugiperda carry insecticide-metabolizing bacteria (IMB) in their gut, some of which are fixed and have a distinct ability to metabolize different insecticides. Thus, we hypothesized that S. frugiperda and its microbiota behave as a single organism (holobiont), and aim to better characterize the IMB and verify their potential in the detoxification and response of this lepidopteran to insecticides. The IMB characterization was achieved through genomic, metatranscriptomic and metabolomic analyses. Our research has enabled the identification of genes and pathways associated with the potential metabolization of toxic compounds by bacteria, as well as aspects of their interaction and evolution with the host. Genome-based taxonomic studies led to a re-evaluation of the IMB taxonomic identities, highlighting the need to reconsider bacterial identification based solely on 16S rRNA sequencing. New bacterial species associated with the gut of S. frugiperda were described: Enterococcus entomosocium n. sp., Enterococcus spodopteracolus n. sp., and Pseudomonas fraudulenta n. sp. The remaining IMB under study were classified as Acinetobacter soli or as different subspecies of the recently described Pseudomonas bharatica. The analyzed IMB showed a remarkable enzymatic repertoire involved in xenobiotic degradation, including carboxylesterases, dehalogenases, and dehydrogenases and, for some of them, detoxification enzymes such as glutathione-S-transferases, superoxide dismutases and peroxiredoxins. Enterococcus, Acinetobacter, and Pseudomonas isolates were found to carry in their genomes the molecular machinery for interacting with the host, including mechanisms for gut colonization, nutrient supply, modulation of the gut microbiota, and interactions with host immune system. However, experiments on gut colonization of S. frugiperda by isolates of Acinetobacter soli and Pseudomonas bharatica suggested that these species may require the host maintenance under insecticide selection pressure to secure the colonization of the host gut. The comprehensive analysis of the response of susceptible and resistant strains of S. frugiperda to the insecticides flubendiamide, spinosad and teflubenzuron highlighted the complex interplay between host phenotype, microbial communities and insecticide exposure on the larval metabolome and on the transcriptional activity of the gut microbiota. The analysis revealed that insecticide exposure and resistance evolution induce metabolic changes that affect host immunity, alter the host\'s interactions with its gut microbial community, and potentially affect associations with associated viruses. Finally, the analysis of the association of E. entomosocium and E. spodopteracolus with other species of the genus Spodoptera revealed that they do not carry enough genetic variation to be separated as taxonomic entities at either the species or subspecies level, showing that these bacteria did not accumulate enough genetic variation after the Spodoptera speciation process due to the process of co-speciation.